Analysis of the spatio-temporal dynamics of incidence, mortality and test rates (rapid and RT-PCR) of COVID-19 in the state of Minas Gerais, Brazil - Silva-Júnior, Milton José da; Mendonça, Kaio Saramago; Lima, Caio Augusto de; Pires, Priscilla Larissa Silva; Calegari, Tatiany; de Stefan, Stefan Vilges de (Revista de Epidemiologia e Controle de Infecção, 2021)
Background and Objectives: A novel type of coronavirus, SARS-CoV-2, is responsible for an unprecedented pandemic with profound socioeconomic consequences. Owing to its recent discovery still represents a great unknown to researchers. Thus, this study aims to establish the spatio-temporal associations of the incidence, mortality, and the rate of both rapid and RT-PCR tests in Minas Gerais. Methods: This is a quantitative analysis of secondary data based on a cross-sectional research design. Incidence, mortality, date of the first notification of COVID-19 and number of rapid and RT-PCR tests were obtained from the sources: “GAL”, “e-SUS VE” and “SES-MG”. Pearson coefficient for correlation was calculated to establish the level of association between the relevant data. Descriptive statistical procedures were used to provide a comprehensive understanding of the distribution of incidence, mortality and test rates in the territory. Results: Positive correlations were found between the rate of rapid tests and incidence; rate of RT-PCR tests and incidence/mortality. At the municipal level, incidence, mortality, rate of rapid tests and RT-PCR revealed a negative correlation with days elapsed since the First Notified Case. The same effect occurs at the level of health macro-regions. Conclusion: The heterogeneity of the incidence and mortality of COVID-19 in the territory of Minas Gerais, as well as the rate of tests may be caused, in part, due to the different dates of introduction of the virus in the municipalities/macro-regions. It is speculated that this phenomenon occurs due to the dynamics of regional and inter-regional flows of people.